Analisis Efektifitas Iklan Djarum Mezzo Di Media Televisi Pada Mahasiswa Fakultas Ekonomi Universitas 17 Agustus 1945 Samarinda - Mardiana., Silvester Roule L.W, LCA Robin Jonathan (EKONOMIA, 2016)
Competition in the tobacco industry increasingly stringent makes PT Djarum must have a strategy so that products can be accepted in the market. In promoting Mezzo Djarum tobacco products are one of them through the medium of television advertising is expected to reach a broad segment of the market even though the cost is very expensive. Pemasalahan are faced is whether advertising Djarum Mezzo in the medium of television has been effective enough to attract the attention of a very broad audience.               The study aims to analyze the effectiveness of television advertising Djarum Mezzo using the EPIC model. This research is a survey research using a questionnaire as a data collection tool. Questionnaire is divided into several parts: profile / demographics of respondents and respondents about the statement-perntaan EPIC dimension which includes the dimensions of empathy, persuasion, and the impact of communication. The sample was 100 respondents from the Faculty of Economics, University August 17, 1945 Samarinda. Methods of data analysis used in this study is a simple tabulation analysis and methods the average score.            The results using the EPIC model analysis of the Djarum Mezzo television advertising shows that the dimensions of empathy while the effective influence of persuasion dimension, impact and influence effective communication. It showed that respondents liked, stating against the Mezzo Djarum advertising and felt that the ad was already good and easily remembered by the audience (the respondent). EPIC rate overall positive assessment, which means that the television advertising Mezzo Djarum cigarettes are effective in scale but has not maximized performance.